Analiza eksergijskih tokov absorpcijske hladilne naprave - Vasić, Vasilije (Strojniški vestnik, 2000)
This paper presents our analysis of the exergy and energy flows and exergy efficiency of an absorption chiller which has been calculated for all areas of the device's exploatation. This analysis has been implemented on a single-stage absorption chiller with LiBr/H20 as a working media. We wish to show the advantages of sorption chillers, in our case absorption chillers, in comparison to compressor chillers in utilizing low exergy, rejected heat and in the use of alternative energy sources.
Keywords: naprave hladilne; naprave absorpcijske; tok energijski; izkoristek eksergijski; absorberji; hlajenje; energijski tokovi; izkoristek